04.23 Identification of a novel subset of pathogenic stromal cells with key effector functions in tissue inflammation and damage. (1st March 2017) - Croft, Adam P; Campos, Joana; Nayar, Saba; Denton, Alice E; Savary, Loriane; Saghir, Atif; Fearon, Doug T; Filer, Andrew; Barone, Francesca; Buckley, Christopher D
Abstract : Background: Stromal cells are key effector cells in tissue inflammation and damage. Despite their importance these cells are yet to be targeted therapeutically. We have previously identified a distinct subset of stromal cells defined by their expression of a cassette of cell surface proteins including Podoplanin/gp38 (PDPN), Fibroblast activation protein (FAP) and Cadherin-11. The aim of this study was to determine the pathogenic role of these cells in tissue inflammation. Methods: Salivary gland inflammation was induced by intra-ductal administration of a replication-deficient adenovirus resulting in tertiary lymphoid structure (TLS) formation as previously described. 1 Polyarthritis was induced using the KRN serum transfer model as previously described. 2 To delete FAP-expressing cells we used a model of conditional depletion of FAP-expressing cells, in which FAP-DTR mice were treated with Diphtheria Toxin Disease severity was assessed clinically, histologically and by MicroCT and a combination of immunofluorescence, quantitative RT-PCR and flow cytometry was performed on digested salivary glands and synovial membrane tissue. Results: Tissue resident stromal cells dynamically express FAP, PDPN and cadherin-11 during inflammation. This cassette of cell surface markers defined a population of stromal cells that expand during inflammation by in situ proliferation. In the salivary gland, these pathogeneic cells are found surrounding ectopic lymphoid aggregates where they produce lymphoid chemokines and survival factors. In the synovium, they are localised to the synovial lining layer and pannus tissue where they invade articular cartilage and bone. Selective deletion of FAP expressing cells resulted in a defect in lymphoid chemokine production, decreased number of infiltrating lymphocytes and severely inhibited TLO formation in the salivary gland. In the joint, therapeutic deletion significantly attenuated synovial inflammation, inflammatory cell infiltration, reduced the severity of arthritis and protected against joint damage. Conclusions: We have identified a pathogenic subset of stromal cells defined by their expression of common cassette of cell surface markers. Whilst the phenotype of these cells is common to inflammation our data suggests their function is both tissue and disease specific. References: 1. Bombardieri, Barone, et al. JI. 2012. 2. Huang, et al. Arthrits Rheumatol2014.